Percepção de gestores sobre as práticas de GRC em projetos públicos: o caso de uma instituição de ensino superior - Silva, Gilson Gomes da (2019)
This paper aims to understand how project managers perceive GRC practices in their projects, based on the perception of professionals who work or have worked, directly or indirectly, in projects linked to a public sector organization. . From the literature, we first obtained a model presented in the theoretical framework that proposes in an integrated way the management of GRC within a holistic approach, that is, that seeks to understand the phenomena in their entirety and globality. According to the authors, most organizations are managing their governance, risk and compliance initiatives in functional silos that do not communicate with each other. A theoretical framework was also obtained showing that PMO, GRC and organizational efficiency are interconnected; where the first two lead to the last one. In this frework, PMO's role is to ensure project management on individual projects and to provide strategic management, relationship management and IT management. Semi-structured interviews were conducted with 3 project managers from the Project Management Secretariat. The analysis method consisted of content analysis (BARDIN, 2011), supported by IRaMuTeQ software for systematization and data description. This thesis argued that deploying GRC in an organization will only be effective if there is GRC management within a holistic approach. That is, the initial assumption, based on the literature, was confirmed by the case study in a higher education institution. It was shown that it is not possible to understand GRC practices without first observing the differences in implementation levels of the themes present in GRC in isolation. What is identified in the present case is that "governance", "risk" and "compliance" are not at the same level of presence in the organization, which makes it difficult to fully use the GRC in the projects of the organization.